Synthesis and evaluation of 2′H-spiro[cyclohexane-1, 3′-imidazo[1, 5-a]pyridine]-1′, 5′-dione derivatives as Mnk inhibitors. Issue 18 (15th September 2019) - Abdelaziz, Ahmed M.; Basnet, Sunita K.C.; Islam, Saiful; Li, Manjun; Tadesse, Solomon; Albrecht, Hugo; Gerber, Cobus; Yu, Mingfeng; Wang, Shudong
Graphical abstract: Abstract: Post-translational modulation of eIF4E through phosphorylation by Mnks is highly integral to the pathogenesis of different cancers. Therefore, inhibition of Mnks offers a strategy for cancer treatment. Herein, a series of 2′ H -spiro[cyclohexane-1, 3′-imidazo[1, 5- a ]pyridine]-1′, 5′-dione derivatives is presented as Mnk inhibitors. Some of them showed sub-micromolar to low nanomolar inhibitory activities against Mnk1/2 with a high level of selectivity for both kinases over CDKs. Biochemical assays revealed that compounds 4c and 4t are non-ATP-competitive inhibitors of Mnks. Lead compound 4t demonstrated a high selectivity for Mnk1/2 over a selection of 51 kinases, and displayed anti-proliferative activities against a panel of cancer cell lines. However, this compound in combination with our in-house CDK4/6 inhibitor 83 did not show a synergistic effect in A2780 ovarian cancer cells, suggesting that caution be exercised in the selection of an agent to be combined with an Mnk inhibitor.